Specific and nonspecific characteristics of the leaf extract of Blumea balsamifera originated from East Java, Indonesia - Putra, I Made Wisnu Adhi; Sandhika, I Made Gde Sudyadnyana (Acta Chimica Asiana, 2024)
Blumea balsamifera extract has been shown to have biological activities such as anti-fungal, anti-tumor, radical scavenger, anti-obesity, hepatoprotective, antioxidant, anti-microbial, anti-inflammatory, antiplasmodial, and wound healing. The quality and efficacy of B. balsamifera extract are determined by its specific and nonspecific characteristics. This study explored the characteristics of B. balsamifera extract through a series of standardization processes. The dried leaves of B. balsamifera were powdered and macerated with 70% ethanol. After the solvent evaporation, a thick extract was obtained and stored in a refrigerator. The specific characteristics tested were organoleptic evaluation, total phenolic content (Folin-Ciocalteu method), total flavonoid content (aluminium chloride colorimetric method), and phytochemical screening using thin layer chromatography. The nonspecific characteristics tested were extraction yield, moisture content, total ash content, and acid-insoluble ash. The results of the study showed that the extraction process resulted in a yield of 13.4%. The extract had a thick and sticky appearance, a dark brown colour, a characteristic aroma, and a bitter taste. The moisture content, total ash content, acid-insoluble ash content, total phenolic content, and total flavonoid content of the extract were found to be 8.33±0.57 %ml/g, 11.63±0.86 %g/g, 2.26±0.12 %g/g, 43.86±0.89 mg GAE/g extract and 25.48±0.42 mg QE/g extract, respectively. Analysis using thin layer chromatography demonstrated that the extract included phenolics, flavonoids, terpenoids, and steroids.